Prairie dog empire : a saga of the shortgrass prairie - Johnsgard, Paul A. (University of Nebraska Press, 2005)
"An indispensable and highly readable introduction to the ecosystem of the shortgrass prairie, Prairie Dog Empire describes in clear and detailed terms the habitat and habits of black-tailed prairie dogs; their subsistence, seasonal behavior, and the makeup of their vast colonies; and the ways in which their "towns" transform the surrounding terrain - for better or worse. Paul A. Johnsgard recounts how this terrain was in turn transformed over the past century by the destruction of prairie dogs and their grassland habitats, together with the removal of the bison and their replacement with domestic livestock